Radiosonde Data from 2008 NABOS Cruise (International Arctic Research Center (IARC) Data Archive)
Radiosonde data collected in the Russian Arctic on board the 'Kapitan Dranitsyn' by Vladimir Alexeev during NABOS (Nansen and Amundsens Basins Observational System) 2008.